Implementasi Model Cooperative Learning Dalam Meningkatkan Kemampuan Berpikir Kritis Pada Pembelajaran PAI Siswa Kelas XI SMA Diponegoro 1 Purwokerto - Yatur Rohmah, Any; Sunhaji, Sunhaji (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The Learning processes commonly used in Islamic Religious Education, such as lectures or memorization, tend to make students passive and provide limited space for critical thinking. This study aims to determine the implementation of the Cooperative Learning model in improving critical thinking skills in Islamic Religious Education learning among 11th-grade students at SMA Diponegoro 1 Purwokerto. This research uses a field research method with a descriptive qualitative approach. The study was conducted at SMA Diponegoro 1 Purwokerto, located at Jl. Letjend Pol. Soemarto Gg. VI No. 63, Karangsuci, Purwanegara, Purwokerto Utara District, Banyumas Regency. The research subjects include the principal, Islamic Religious Education teacher, and 11th-grade students. The results of the study show that Islamic Religious Education learning at SMA Diponegoro 1 Purwokerto has applied the Cooperative Learning model. The type used by the teacher is Numbered Heads Together (NHT). This model is used to increase participation in group discussions and encourage critical thinking skills through collaboration and individual responsibility within the group. In implementing the Numbered Heads Together type of Cooperative Learning model, the teacher carries out three stages: preparation, implementation, and conclusion. The implementation of the Cooperative Learning model with the NHT type runs effectively. Students show improvement in critical thinking activities, as seen from their active participation in group discussions, ability to express opinions, and skills in solving problems logically and systematically.